Attitude towards learning French literature in person: the case of the UCR - Cambronero Artavia, María del Pilar (2025)
In a context of frequent questioning of the utility of humanistic studies, French and French Teaching degree students may see altered their motivation towards reading and learning literature. The present study staged the attitude of the students towards the literature courses they received in virtual mode during the years 2021 and 2022, as well as the way in which the experience of moving to the face-to-face mode had an impact on their motivation and their learning. Thanks to the application of questionnaires within a qualitative research, it was possible to collect the students’ perceptions about the effectiveness of the knowledge acquired according to the learning modality, which demonstrated the importance of the role of the teacher in the approach to literature, the relevance of the face-to-face modality in the courses to enhance the teaching capabilities and the proficiency of the students, the convenience of showing aspects merely related to the implications of reading and the need for the involvement of the students in their learning process.